Implications of carbon Taxing policies on the food supply chain in Canada - Sylvain Charlebois; Gumataw Abebe; Tony R. Walker; Vlado Keselj; Janet Music; Keshava Pallavi Gone; Karim Tuffaha; Janele Vezeau; Bibhuti Sarker; Stacey Taylor (Transportation Research Interdisciplinary Perspectives)
This paper explores the implications of carbon-taxing policies on food supply chain affordability and competitiveness in Canada. Initiated with Alberta’s 2007 carbon levy, Canada’s approach to carbon taxation aims to mitigate greenhouse gas emissions while addressing the economic impacts on the food sector. With the federal carbon price set to rise to CAD $170 per ton by 2030, the study investigates the potential for increased food prices and the challenges to food affordability as well as identify the current gaps in understanding the intricacies of Carbon Taxing Policies on the Food Supply Chain in Canada. Graphic analyses and forecasts were created using data from Statistics Canada and the U.S. Census Bureau. The main findings of the analyses reveal shifts in wholesale and industrial prices since the carbon tax’s implementation. Findings suggest that carbon pricing may be affecting every level of the food supply chain, highlighting the need for further research to understand its full impact on food affordability and security.